#TITLE_ALTERNATIVE# - TERISSA (NIM : 20911008)Pembimbing :Dr. Agus Yodi Gunawan, HANIFA
In this thesis, the SPH method is used to model and simulate the Poiseuille flow of Newtonian fluid within a channel with various formation of obstacles. In this method, the position of each particle can be calculated for each time step. Boundary conditions of the simulation are no-slip conditions as the channel bounded by two fixed parallel plates and applied pressure difference between inlet and outlet. The Poiseuille flow simulation is carried out for five types formation of obstacles inside the channel. Hence, the velocity profile is analyzed for each condition. The simulations show that the greater or more obstacles inside the channel will create slower terminal velocity than the terminal velocity flow without obstacles.